Transforming the Legendary Image of the Legislator as Promoter of Non-violation of Animal Life: a Shared Premise in Plutarch’s Moralia and Porphyry’s De Abstinentia - Gamlath, Isha (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2024)
Legislation was a component that characterized the link between civic and religious authority throughout the Archaic period to the early Roman Empire. Legislation is much celebrated in the respective philosophical cultures of Plutarch and Porphyry: in the former, the image of the ideal ruler reflects the notion of a philosopherking, while in the latter, it was attached with significance to life lived under the divine law of the Intellect of Kronos. This article will demonstrate how Plutarch and Porphyry jointly acknowledge the legislator’s legendary image as more than mediating between hostile factions of the citizen body and regulating divine worship and ritual praxis, often on the basis of his political expertise and divine ancestry by casting it in a fresh mold. In doing so, Plutarch and Porphyry together claim that the legislator’s legendary image plays a decisivly corrective role in ancient society by way of introducing the non-violation of animal life for food and sacrifice. This corrective role will be discussed as being pivotal for the intellectual pursuit of the priestly community and philosophers in selected dialogues in Plutarch’s Moralia and Porphyry’s De Abstinentia.